Millennials Beauty Cosmetics / Nur Aisyah Diyanah Norfazali - Nur Aisyah Diyanah, Norfazali (2020)
Millennials Beauty Cosmetics is a start-up venture business producing and selling specializing healthy cosmetics based on natural ingredients, organic ingredients and herbal ingredients products named Sutera Lipglass and Sutera Lipserum that founded by Aisyah Diyanah. The mission is to build a highly successful, profitable all-round business of healthy cosmetic followed by the vision to to become the number one choice in the whole world. The headquarters (HQ) is in Malacca, Malaysia. This business has been able to secure a long-term lease for a facility in a strategic location with an option of a long-term renewal on an agreed terms and conditions that is favourable to us. This location was chosen because Malacca is a city with an abundance of breath-taking sights and rich heritage of a major attractions for tourists to get around on foot or trishaw to explore the many places that make it unique. Thus, this is a golden opportunity for this business to thrive. It offers beauty supply products to customers interested in cosmetics. The facility has government approval for the kind of business that wanted to run, and it is easily accessible, and we are deliberate about that to facilitate easy movement of raw materials and finished cosmetic products. Sutera Lipglass and Lipserum is made from organic, natural ingredients. Some of the ingredients are organic and have high value because we also infused quite several essential oils. Herbal based product is very rare and herbal benefit is infinity. Sutera Lipserum is a colourless and Sutera Lipglass that have mineral color pigmen while both are no paraben, not tested on animals and vegan friendly product. Starting a cosmetic is a very easy business to start and it is not so capital intensive- especially if you choose to start on a small scale in a small community. Getting the right brands that people want to buy and good stock keeping records are the secrets of running a retail business such as cosmetics. In other to achieve this, we aware that it takes a business with the right employees and structure to achieve all what we have set to achieve, which is why will be putting structures and standard operating processes in place that will help us meet our clients demand and keep running the business.